Electrochemical Oxidation and Determination of Antiviral Drug Acyclovir by Modified Carbon Paste Electrode With Magnetic CdO Nanoparticles - Naghian, Ebrahim; Marzi Khosrowshahi, Elnaz; Sohouli, Esmail; Pazoki-Toroudi, Hamid Reza; Sobhani-Nasab, Ali; Rahimi-Nasrabadi, Mehdi; Ahmadi, Farhad (Frontiers in Chemistry, 2020)
With the development of nanomaterials in electrochemical sensors, the use of nanostructures to modify the electrode surface has been shown to improve the kinetics of the electron transfer process. In this study, a sensor was developed for the electrochemical determination of Acyclovir (ACV) based on the modified carbon paste electrode (CPE) by CdO/Fe3O4. The magnetic CdO nanoparticles characterization was studied by energy-dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD). To study of the modified CPE surface morphology, scanning electron microscopy (SEM) was used. At the optimal conditions, a noteworthy enhancement in the electrochemical behavior of ACV was observed at the surface of the modified CPE compared to the unmodified CPE. A detection limit of 300 nM and a linear range of 1 to 100 μM were obtained for the quantitative monitoring of ACV at the modified CPE surface using differential pulse voltammetry (DPV) in phosphate buffer. The RSD% (relative standard deviation) of the electrode response were less than 4.3% indicating development of a high precision method. Also, satisfactory results were obtained in the determination of ACV with the modified electrode in tablet, blood serum and urine samples with a satisfactory relative recovery (RR%) in the range of 94.0 to 104.4%.